Speaking and writing the Anthropocene: in conversation with Cecil Rajendra - Mustafa Kamal, Muhammad Syaukat; Zainal, Zainor Izat; Omar, Noritah (Faculty of Arts and Social Sciences, UM, 2024)
Cecil Rajendra, nicknamed “The Lawyer-Poet”, is one of Malaysia’s most prominent literary writers. A lawyer by profession and a poet with over 20 published collections, his literary contributions were recognized with a nomination for the Nobel Prize in Literature in 2005. His poems have been featured in multiple media forms including magazines, journals, newspapers, BBC educational programs and textbooks all over the world. He has been expressing concerns about the destruction of nature long before it became a mainstream concern. Most of his environmental poems are found in Dove on Fire: Poems of Peace, Justice and Ecology (1987) and Rags & Ragas (2000), while some of his recent ones include Limericks & Lyrics from a Lockdown (2021), and “Half-Past Doomsday Hour” published in the Sunday Star in 2022. We find it important to interview him, having contributed so much to the local literary scene as well as many legal cases related to the environment. The present interview revolves around his literary career, the relationship between his works and the environment, his motivations and his views on the Anthropocene.